Import Demand of Palm Oil From Indonesia in The Indian Market - bin Abdullah, Zainuddin (Jurnal Manajemen dan Agribisnis, 2024)
Palm oil has occupied an important position in the world trade of edible oils. India is still very dependent on palm oil imports, including other vegetable oils, to meet the needs of cooking oil and palm-based food industries. This study uses an ARDL approach to examine several factors that affect the demand for palm oil imports (CPO and RPO) from Indonesia in the Indian market. In the long run, CPO imports in the Indian market are significantly affected by CPO prices, sunflower oil prices, soybean oil prices, import tariffs, real exchange rates, real income per capita, soybean oil production in India, and India's population. Indonesian RPO imports in the Indian market are also significantly influenced by import price, soybean oil price, import tariff, and total vegetable oil production in India. Indonesia should be able to capitalize on the Indian market as its demand for vegetable oil is increasing. The increasing size of the Indian market (although more protective) is a challenge for Indonesia to meet the demand for vegetable oil in the Indian market. Indonesia's industrial and trade policy should shift the structure of India's import demand from CPO to palm oil-based downstream semi-finished and final products. Keywords: import demand, crude palm oil, refined palm oil, Indonesia, Indian market